An Investigation of Expectation Gap between Independent Auditors and Users from Auditing Services Related to the Quality of Auditing Services Based on Their Role and Professional Features - Fatah Behzadian; Naser Izadi Nia (Asian Journal of Accounting Research, 2017)
In this research, using an analytical framework on factors affecting the quality of auditing services, we consider factors that affect an expectations gap in providers and users of auditing services related to factors affecting auditing quality. Effective factors studied in this regard are professional features, including the professional role of individuals in the auditing process (auditors against preparers of financial statements), professional experience of individuals, professional rating and size of auditing firms. The first statistical society consists of certified public accountants (CPAs) working in the auditing organization and audit firms in Iran, and the second statistical society consists of all investment companies that operate under the supervision of the Tehran Stock Exchange Organization. Based on the results of the research, the role of professionals in the auditing process is not effective as an independent auditor or financial statements provider, as well as the professional experience of individuals in the expectations gap from factors affecting auditing quality, while the size and qualities of the auditing firms were influenced by the expectations gap of individuals in the field of auditing regulation.